White matter hyperintensities quantification in healthy adults: a systematic review and meta-analysis - Melazzini, L; Vitali, P; Olivieri, E; Bolchini, M; Zanardo, M; Savoldi, F; Di Leo, G; Griffanti, L; Baselli, G; Sardanelli, F; Codari, M (Wiley, 2020)
Background Although white matter hyperintensities (WMH) volumetric assessment is now customary in research studies, inconsistent WMH measures among homogenous populations may prevent the clinical usability of this biomarker.